Wiley encyclopedia of computer science and engineering. - Wah, Benjamin W., ....- (Hoboken : Wiley, 2009)
Includes over 450 A to Z articles addressing the latest advances and findings in computer science and engineering, in addition to important topics of interest to computer scientists and engineers, including standards, electronic commerce, financial engineering, and computer education.